Selection of young soccer players in terms of anthropometric and physiological factors - Gil, S.; Ruiz, F.; Irazusta, A.; Gil, J.; Irazusta, J. (The Journal of Sports Medicine and Physical Fitness, 2007)
Aim: The aim of this paper was to describe the anthropometric and physiological characteristics of young soccer players (14-17 years old) which were associated with their being successful or not as soccer players. Methods: Somatotype and body composition was calculated by measuring skinfolds, limb circumferences and joint diameters. V.O2max was estimated by the Astrand's Test. Sprint, jump and endurance tests were also performed. Results: The most relevant differences were obtained between selected and non-selected players belonging to the 14-year-old team. Selected players were taller, heavier, leaner and faster and they had higher absolute or relative V.O2max. In addition, a higher % of selected players was found among those born during the first 6 months of the year. In the rest of the teams, the agility was better in selected than in non-selected players. At later ages, there was also a predominance of players born during the first 6 months of the year. Conclusion: These results indicate that around the time of puberty, parameters associated with physical maturity such as height, size, speed, V.O2max, or chronological age are important to determine the success of a soccer player. At older ages, other factors such as agility seem to be more important. Nevertheless, players born in the 1st semester of the year are also more frequent in the older teams. These findings should be taken into account by trainers and coaches, in order to avoid biasing their selection choices.